MODEL PENILAIAN DAMPAK NEGATIF METODE KONSTRUKSI STRUKTUR ATAS JALAN LAYANG DI PERKOTAAN PADA LINGKUNGAN SEKITAR - Winarso, Setya
Urban fly over construction often causes an environmental change that suffers a loss to people and traffic users around the construction site. This change is called a negative impact. One source of the negative impact is the consequences of the construction method which been implemented. The examples of this negative impact are traffic jam, noise, injury, etc. This thesis is intended to create a rating model that has a procedure to appraise a negative impact of construction method of fly over project in the urban areas. This rating model can be used to describe a distribution grade of negative impact on each applicable construction method of fly over design, which can help engineer in the design stage to anticipate the negative impact. A case study of the proposed rating model was performed on Cideng Caringin Fly Over Plan. The result of this case study shows that this model still needs a comprehensive assessment from the experts, particularly to determine weight and value of negative impact contribution variables related to environment condition of the construction site .